HUBUNGAN RELIGIUSITAS DAN SELF-CONTROL TERHADAP KEPUTUSAN BERPACARAN - Tengku Nuranasmita (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the role of human resource optimization in improving the quality of public services through a literature review approach. The research employed a qualitative method using a library research approach by examining relevant scientific journals, books, legislation, and policy documents. The findings indicate that human resource optimization can be achieved through competency development, continuous training, strengthening work ethics, professional development, and the implementation of an integrated performance management system. In addition, transformational leadership, an adaptive organizational culture, and public service motivation significantly contribute to improving service quality. The implementation of the New Public Service principles also encourages public officials to deliver services that are more responsive, accountable, and citizen-oriented. The study concludes that human resources are a strategic factor in achieving high-quality public services. Therefore, sustainable, systematic, and well-planned human resource development policies are essential to enhance the capacity of public officials and improve the quality of services provided to the community.